A Critique on the Proposed Use of External Sovereign Credit Ratings in Basel II - Roman Kraeussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This paper deals with the proposed use of sovereign credit ratings in the Basel Accord on Capital Adequacy (Basel II) and considers its potential effect on emerging markets financ-ing. It investigates in a first attempt the consequences of the planned revisions on the two central aspects of international bank credit flows: the impact on capital costs and the volatility of credit supply across the risk spectrum of borrowers. The empirical findings cast doubt on the usefulness of credit ratings in determining commercial banks' capital adequacy ratios since the standardized approach to credit risk would lead to more divergence rather than conver-gence between investment-grade and speculative-grade borrowers. This conclusion is based on the lateness and cyclical determination of credit rating agencies' sovereign risk assess-ments and the continuing incentives for short-term rather than long-term interbank lending ingrained in the proposed Basel II framework.
urn:nbn:de:hebis:30-10283
Keywords: E44; E47; G15; 330; Sovereign Risk; Credit Ratings; Basel II